Cases of Code-Switching on Facebook Comments of Public School Teachers in the Philippines: Its Implications to Classroom Teaching and Language Policies - Gerald Calicdan Arugay (SEAMEO QITEP in Language, 2023)
Code-switching is a linguistic phenomenon where speakers switch between two or more languages during a conversation. This study investigates cases of code-switching among public school teachers in the Philippines and its implications for classroom teaching and language policies. The study used a mixed-methods research design, combining qualitative and quantitative approaches. Data was collected from Facebook comments and replies of teachers belonging to a Facebook group exclusive for public school teachers in the Philippines, with 730,480 members. The findings showed that code-switching is prevalent among teachers, and the most common types of code-switching are inter-sentential and intra-sentential switching. The study contributes to the understanding of code-switching and its role in communication, particularly in the educational context.